TcMYB73, a salicylic acid-responsive R2R3-MYB transcription factor, positively regulates paclitaxel biosynthesis in Taxus chinensis in direct and indirect ways - Yifei Ren; Donglin Liu; Weicheng Zhao; Xinran Wang; Xiaoying Cao; Wen Wan (BMC Plant Biology)
Abstract Background Paclitaxel (Taxol) is an invaluable secondary metabolite extracted from Taxus species, wildly utilized in cancer therapeutics. Salicylic acid (SA), an important phytohormone, substantially elevates paclitaxel accumulation in Taxus cell suspension cultures. However, the molecular mechanisms governing SA-induced modulation of paclitaxel biosynthesis remain poorly elucidated. Our previous studies identified TcMYB73, an SA-responsive R2R3-MYB transcription factor (TF), which demonstrates a robust positive correlation with paclitaxel biosynthesis, implying its orchestrating role in this metabolic pathway. Results Expression pattern analysis revealed that TcMYB73 displays predominant expression in lateral roots. Both overexpression and RNA interference (RNAi) of TcMYB73 demonstrated its regulatory function in modulating key paclitaxel biosynthetic genes, including taxadiene synthase (TASY), 10-deacetylbaccatin III-10-O-acetyltransferase (DBAT), and 3’-N-debenzoyl-2’-deoxytaxol-N-benzoyltransferase (DBTNBT). Transient TcMYB73 overexpression in Taxus chinensis (T. chinensis) needles induced 2.38-, 2.87-, and 1.79-fold increases in 10-DAB, baccatin III, and paclitaxel accumulation, respectively, compared to controls. Additionally, yeast one-hybrid (Y1H), Electrophoretic Mobility Shift Assay (EMSA), chromatin immunoprecipitation-quantitative PCR (ChIP-qPCR), and dual-luciferase (Dual-LUC) assays verified that TcMYB73 directly binds to MYB recognition elements in the T10OH promoter, enhancing its transcription. Furthermore, TcWRKY33, a transcriptional activator of DBAT, functions as a positive regulator mediating SA signaling within the paclitaxel biosynthetic pathway. Subsequent investigations validated that TcMYB73 upregulates DBAT expression via direct transcriptional activation of TcWRKY33. Collectively, these results demonstrate that TcMYB73 transduces SA signals to T10OH and TcWRKY33, coordinately regulating paclitaxel biosynthesis through dual mechanisms: direct activation of biosynthetic genes and indirect modulation of upstream regulators. Conclusions Our results indicated that the SA-responsive R2R3-MYB TF, TcMYB73 transcriptionally governs paclitaxel biosynthesis in T. chinensis through direct activation the expression of the T10OH gene, and activating TcWRKY33 expression, thereby modulating DBAT expression. This study provides mechanistic insights into the role of TcMYB73 in mediating SA-induced transcriptional regulation of paclitaxel biosynthesis in Taxus species.